Specific in vitro adenylylation of the simian virus 40 large tumor antigen. - Bradley, M K (1984)
Incubation of the simian virus 40 (SV40) large tumor antigen (T) from either transformed or lytically infected cells with adenosine [8-3H]-, [alpha-32P]-, or [alpha-[35S]thio]-triphosphate in the presence of Mg2+ resulted in its labeling as defined by the appearance of an intact, appropriately immunoreactive band in NaDodSO4/polyacrylamide gels. Radioactivity remained associated with the protein after boiling in buffer containing 3% NaDodSO4, and 2-mercaptoethanol as well as after heating in 0.1 M HCl, 0.1 M NH4OH, or hydroxylamine, but it was dissociated after incubation in 0.1 M NaOH at 37 degrees C. After limited boiling of gel-purified [alpha-32P] ATP + T complex in 5.6 M HCl, o-[32P]phosphoserine was released, and snake venom phosphodiesterase or 0.5 M piperidine treatment of such a complex resulted in the liberation of [alpha-32P]AMP. The reaction proceeded when either purified, soluble T or insoluble, specifically immunoprecipitated antigen was used as substrate. ATP and dATP were the preferred nucleotide substrates by comparison with the other six standard ribonucleoside or deoxynucleoside triphosphates. Partial tryptic digests of T + [alpha-32P]ATP complexes revealed the presence of a single labeled peptide of Mr approximately equal to 12 - 14 X 10(3), and after exhaustive digestion, there was a single radioactive spot in the fingerprint. These data indicate that T can be adenylylated at a specific seryl residue(s) in a limited portion of the protein surface. Furthermore, adenylylation appears to be reversible and to proceed by a pyrophosphorylytic mechanism, since the nucleotide was released from the protein following incubation of adenylylated T with Mg2+, sodium pyrophosphate, and poly(dT).